Accumulation of STIM1 is associated with the degenerative muscle fibre phenotype in ALS and other neurogenic atrophies. (April 2015) - Goswami, Anand; Jesse, Christofer Marvin; Chandrasekar, Akila; Bushuven, Eva; Vollrath, Jan Tilmann; Dreser, Alice; Katona, Istvan; Beyer, Cordian; Johann, Sonja; Feller, A. C.; Grond, M.; Wagner, S.; et al.
Abstract : Aim: Upon denervation, skeletal muscle fibres initiate complex changes in gene expression. Many of these genes are involved in muscle fibre remodelling and atrophy. Amyotrophic lateral sclerosis (ALS) leads to progressive neurodegeneration and neurogenic muscular atrophy (NMA). Disturbed calcium homeostasis and misfolded protein aggregation both in motor neurones and muscle fibres are key elements of ALS pathogenesis that are mutually interdependent. Therefore, we hypothesized that the calcium sensor STIM1 might be abnormally modified and involved in muscle fibre degeneration in ALS and other types of NMA. Methods: We examined ALS and NMA patient biopsy and autopsy tissue and tissue from G93A SOD1 mice by immunohistochemistry and immunoblotting. Results: In normal human and mouse muscle STIM1 was found to be differentially expressed in muscle fibres of different types and to concentrate at neuromuscular junctions, compatible with its known role in calcium sensing. Denervated muscle fibres of sALS and NMA cases and SOD1 mice showed diffusely increased STIM1 immunoreactivity along with ubiquitinated material. In addition, distinct focal accumulations of STIM1 were observed in target structures within denervated fibres of sALS and other NMA as well as SOD1 mouse muscles. Large STIM1‐immunoreactive structures were found in ALS‐8 patient muscle harbouring the P56S mutation in the ER protein VAPB. Conclusion: These findings suggest that STIM1 is involved in several ways in the reaction of muscle fibres to denervation, probably reflecting alterations in calcium homeostasis in denervated muscle fibres.